Nursing in the Royal Chamber between the Middle Age and the Modern Age: healthcare in the Court of Enrique IV and Isabel of Valois - Francisco Javier Crespo Muñoz; Esperanza Luque Sánchez; Guillermo A. Cañadas de la Fuente; A. González García (Universidad de Alicante, 2012)
Healthcare in the court was something fundamental. The different health professionals had as their objective to watch over the health of everybody who belonged to it. Something that everyone of them carried out depending on their abilities and their knowlegde. The work that we propose is based on the information found in the section of Casas y Sitios Reales of the Archivo General de Simancas. There, we could find information about the services provided to Enrique IV and Isabel of Valois during their respective reigns, among other monarchs. Once we had the information analyzed we could confirm the objectivity of a methodical work when it came to provide the care needed, as well as the application of treatments by the health workers, more specifically, nurses.